A closed-loop life cycle assessment of recycled aggregate concrete utilization in China. (October 2016) - Ding, Tao; Xiao, Jianzhuang; Tam, Vivian W.Y.
Highlights: A closed-loop LCA on RAC utilization in China with entire local LCI is performed. Comparative results on environmental impact between NAC and RAC is achieved. Possible opportunity for lowering environmental impact of RAC is proposed. Abstract: This paper studies the potential environmental impact of recycled coarse aggregate (RCA) for concrete production in China. According to the cradle-to-cradle theory, a closed-loop life cycle assessment (LCA) on recycled aggregate concrete (RAC) utilization in China with entire local life cycle inventory (LCI) is performed, regarding the environmental influence of cement content, aggregate production, transportation and waste landfilling. Special attention is paid on the primary resource and energy conservation, as well as climate protection induced by RAC applications. Environmental impact between natural aggregate concrete (NAC) and RAC are also compared. It is shown that cement proportion and transportation are the top two contributors for carbon dioxide (CO2 ) emissions and energy consumption for both NAC and RAC. Sensitivity analysis also proves that long delivery distances for natural coarse aggregate (NCA) leave a possible opportunity for lowering environmental impact of RAC in China.